2022
DOI: 10.3389/fmolb.2022.870395
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-EGFR Monoclonal Antibody in mCRC Maintenance Therapy

Abstract: Background: Epidermal growth factor receptor (EGFR) monoclonal antibodies (mAbs) combined with chemotherapy in patients with RAS (rat sarcoma viral oncogene homolog) wild-type metastatic colorectal cancer (mCRC) can alleviate and stabilize the disease, effectively prolong the progression-free survival (PFS) and overall survival (OS), and improve the overall response rate (ORR), which is the first-line treatment standard scheme for RAS wild-type mCRC currently. However, whether anti-EGFR mAb can be used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Combination chemotherapy has been regarded as the cornerstone for mCRC management [ 9 ]. Furthermore, anti-EGFR monoclonal antibodies (mAbs), such as Cetuximab, have proven to be an effective clinical therapy for mCRC patients with wild type KRAS tumors, and prolonged survival for 10–20% of patients [ 4 ]. One particular trial (CRYSTAL), revealed that the application of cetuximab and FOLFIRI can increase overall survival (OS) by 8.2 months and reduce the risk of progression by 15% in patients with KRAS wild type mCRC compared to FOLFIRI alone [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination chemotherapy has been regarded as the cornerstone for mCRC management [ 9 ]. Furthermore, anti-EGFR monoclonal antibodies (mAbs), such as Cetuximab, have proven to be an effective clinical therapy for mCRC patients with wild type KRAS tumors, and prolonged survival for 10–20% of patients [ 4 ]. One particular trial (CRYSTAL), revealed that the application of cetuximab and FOLFIRI can increase overall survival (OS) by 8.2 months and reduce the risk of progression by 15% in patients with KRAS wild type mCRC compared to FOLFIRI alone [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in RAS, BRAF wild and MSS tumors, cytotoxic/cytostatic chemotherapy (5-FU), Vascular Endothelial Growth Factor Inhibitor (VEGF), and Multi-Kinase targeted agents, in addition to targeted monoclonal antibodies (against Epidermal Growth Factor Receptor (EGFR), have been widely used as the leading treatment modality against metastatic CRC (mCRC) [ 2 , 3 ]. Indeed, EGFR targeted therapy was found to increase overall survival by 10–20% in colorectal cancer [ 4 ]. However, resistance to this therapy was inevitable with the emergence of KRAS and BRAF mutations, driven by intrinsic and extrinsic mechanisms affecting both cellular pathways and tumor microenvironment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, EGFR can regulate the activity of a variety of genes and participate in the occurrence, development and apoptosis and other physiological processes of tumors. Although anti-RGFR monoclonal antibody therapy represented by cetuximab and panitumumab has achieved expected clinical efficacy, most CRC patients develop varying degrees of drug resistance after 5-8 months of treatment, which significantly reduces the clinical benefit of anti-RGFR therapy ( 26 ). Since then, experts in this field have shifted their research focus to the molecular mechanism and prevention strategies of anti-EGFR drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…After induction chemotherapy combined with bevacizumab, fluoropyrimidine maintenance with or without bevacizumab significantly improves PFS and reveals a trend toward prolonged OS and, hence, should be considered [I, B] [ 59 ]. Randomized phase II studies have shown an increase in efficacy with 5-fluorouracil with anti-EGFR MoAb maintenance versus anti-EGFR or 5-fluorouracil in monotherapy (II, B) [ 60 ].…”
Section: Unresectable Disease: First-line Therapymentioning
confidence: 99%